PENINGKATAN MODEL THINK PAIR SHARE BERBANTUAN WHEEL OF TIME TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA SD - Alya Giri Salsabila; Zulmi Roestika Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the differences and the effect of implementing the Think Pair Share (TPS) learning model assisted by the Wheel Of Time media on students’ mathematical concept understanding in Grade II of SD Negeri Lemahireng 01. The research problem is based on students’ low conceptual understanding, indicated by difficulties in explaining, comparing, and applying mathematical concepts, which are caused by teacher-centered learning and the limited use of interactive learning media. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The research subjects consisted of two classes: Class II A as the experimental group, which applied the TPS model assisted by the Wheel Of Time media, and Class II B as the control group, which applied the TPS model without media. Data were collected through concept understanding tests, questionnaires, observations, and documentation. Data analysis techniques included normality tests, homogeneity tests, independent sample t-tests, and simple linear regression analysis. The results showed a significant difference in students’ conceptual understanding between the experimental and control groups. Furthermore, the regression analysis indicated that the Think Pair Share (TPS) learning model assisted by the Wheel Of Time media had a significant effect on improving students’ mathematical concept understanding. The implementation of this learning model increased student activeness, encouraged learning interactions, and helped students understand mathematical concepts more concretely and meaningfully. Therefore, the Think Pair Share learning model assisted by the Wheel Of Time media is effective in improving mathematical concept understanding among Grade II elementary school students.